PENGARUH MEDIA PEMBELAJARAN WORDWALL TERHADAP MOTIVASI BELAJAR SISWA PADA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTS JANNATURROICHAN JOMBANG - Igfirotum Muniroh; Surojudin, Didin (As-Sulthan Journal of Education, 2025)
The aim of this research is to determine the effect of wordwall learning media on learning motivation in class VIII morals lessons at Mts Jannaturroichan. In the teaching and learning process in schools today, it is often found that students have difficulty understanding the learning material provided by the teacher. This is caused by various factors, including a lack of teacher creativity in using methods or strategies in teaching, delivering material that is less interesting, causing learning to become monotonous and making students quickly feel bored and have no motivation to learn. This research uses experimental research with a one group pretest posttest design. The sample for this research was the entire class VIII, totaling 35 people. The instrument used is a saturated sampling technique, namely determining which members of the population are sampled. Data collection was carried out through observation, pretest, posttest and documentation. And the results of data processing after the research were managed statistically starting from the normality test, homogeneity test, Wilcoxom matched pair test and N-Gain test with the help of SPSS 22. Based on the results of data processing in the Wilcoxom matched pair test, Ha was accepted with a significance of 0.000 < 0.05 which means that there is an influence of wordwall learning media on students' learning motivation in moral belief lessons in class VIII. And for the level of motivation, there was an increase in learning motivation after using the wordwall learning media which was obtained at 0.8247. The test results strengthen the statement regarding students' learning motivation in class VIII moral beliefs lessons.